Measuring Global Signals in the Potential Gradient at High Latitude Sites - Tacza, José; Nicoll, Keri A.; Macotela, Edith L.; Kubicki, Marek; Odzimek, Anna; Manninen, Jyrki (Frontiers in Earth Science, 2021)
Previous research has shown that the study of the global electrical circuit can be relevant to climate change studies, and this can be done through measurements of the potential gradient near the surface in fair weather conditions. However, potential gradient measurements can be highly variable due to different local effects (e.g., pollution, convective processes). In order to try to minimize these effects, potential gradient measurements can be performed at remote locations where anthropogenic influences are small. In this work we present potential gradient measurements from five stations at high latitudes in the Southern and Northern Hemisphere. This is the first description of new datasets from Halley, Antarctica; and Sodankyla, Finland. The effect of the polar cap ionospheric potential can be significant at some polar stations and detailed analysis performed here demonstrates a negligible effect on the surface potential gradient at Halley and Sodankyla. New criteria for determination of fair weather conditions at snow covered sites is also reported, demonstrating that wind speeds as low as 3m/s can loft snow particles, and that the fetch of the measurement site is an important factor in determining this threshold wind speed. Daily and seasonal analysis of the potential gradient in fair weather conditions shows great agreement with the “universal” Carnegie curve of the global electric circuit, particularly at Halley. This demonstrates that high latitude sites, at which the magnetic and solar influences are often present, can also provide globally representative measurement sites for study of the global electric circuit.